Pengaruh Literasi Keuangan dan Kemajuan Teknologi terhadap Keputusan Investasi - Krisnahadi, Tama; Ilham, Edinur; Utiarahman, Nurnaningsih; Sutisna, Eka; Mutmainah, Mutmainah (Jurnal EMT KITA, 2026)
The study aims to empirically test the influence of financial literacy and technological advancement on the investment decisions of students at University X in Pekalongan. This study uses a causal associative approach and quantitative methods. Students at University X in Pekalongan serve as the population in this study. The research sample consisted of 117 students selected using a census. A survey method was used for data collection, with students given questionnaires to complete. SmartPLS was used for data analysis, which employed Partial Least Squares-Structural Equation Modeling (PLS-SEM). Based on the research findings, financial literacy and technological advancement have a positive and significant influence, both partially and simultaneously, on the investment decisions of students at PTS X in Pekalongan.